ACTOR NETWORK IN THE IMPLEMENTATION OF THE FREE NUTRITIONAL MEAL PROGRAM (MBG): EVIDENCE FROM TANJUNGPINANG CITY - Fery Andana; Alfiandri; Wayu Eko Yudiatmaja (RADJA PUBLIKA, 2026)
The Free Nutritious Meals Program (MBG) represents one of the largest national nutrition initiatives implemented simultaneously across regions in Indonesia. Although the program is designed through a centralized policy framework, its implementation requires coordination among multiple actors operating across institutional and sectoral boundaries at the local level. Existing studies on policy implementation have largely focused on administrative capacity and institutional design, while limited attention has been given to how relationships among actors shape governance processes in large-scale public nutrition programs. This study examines how actor networks shape the implementation of the MBG program in Tanjungpinang City. A qualitative research design was employed to explore relational dynamics among actors involved in the program. The analysis integrates Actor Network Theory to examine processes of network formation with Social Network Analysis to map relational structures and identify actors occupying strategic positions within the implementation network. Data were collected through in-depth interviews and analysis of policy documents. The findings reveal that MBG implementation is sustained not primarily by formal administrative hierarchy but by a relational governance network connecting actors responsible for food production, service distribution, and regulatory supervision. The Municipal Education Office functions as the central coordination hub within the network, while the Health Office provides regulatory legitimacy and intermediary actors facilitate coordination across institutional levels. These findings suggest that the effectiveness of complex public service programs depends on the capacity of actor networks to develop adaptive relational mechanisms that sustain coordination in diverse local contexts.